Comprehensive immune profiling of SARS-CoV-2 infected kidney transplant patients - Fenninger, Franz; Sherwood, Karen R.; Wu, Vivian; Wong, Paaksum; DeMarco, Mari L.; Wang, Meng; Benedicto, Vincent; Dwarka, Krishna A.; Günther, Oliver P.; Tate, Logan; Yoshida, Eric; Keown, Paul A.; et al. (Frontiers in Transplantation, 2023)
The immune responses of kidney transplant recipients against SARS-CoV-2 remains under studied. In this prospective pilot study, we performed comprehensive immune profiling using cellular, proteomic, and serologic assays on a cohort of 9 kidney transplant recipients and 12 non-transplant individuals diagnosed with COVID-19. Our data show that in addition to having reduced SARS-CoV-2 specific antibody levels, kidney transplant recipients exhibited significant cellular differences including a decrease in naïve - but increase in effector T cells, a high number of CD28+ CD4 effector memory T cells, and increased CD8 T memory stem cells compared with non-transplant patients. Furthermore, transplant patients had lower concentrations of serum cytokine MIP-1β as well as a less diverse T cell receptor repertoire. Overall, our results show that compared to non-transplant patients, kidney transplant recipients with SARS-CoV-2 infection exhibit an immunophenotype that is reminiscent of the immune signature observed in patients with severe COVID-19.